Exploring medical students’ attitudes on computational thinking in a Saudi university: insights from a factor analysis study - Althewini, Abdulaziz; Alobud, Omar (Frontiers in Education, 2024)
Computational thinking represents an innovative pedagogical paradigm embraced by numerous academic institutions to cultivate the problem-solving acumen of students. Despite its widespread acceptance across diverse disciplines, the integration of computational thinking within medical education remains incomplete. This study seeks to ascertain the attitudes of medical university students in Saudi Arabia regarding computational thinking. Employing an exploratory research design, the investigation encompassed 394 health sciences students, transcending educational backgrounds and gender, with the objective of gaging their attitudes and awareness concerning the value, learning, and perceived difficulty associated with computational thinking within the context of medical curricula. The findings of the study indicate a notably positive disposition among students enrolled in medicine and health informatics programs toward computational thinking, surpassing the attitudes observed in other health disciplines. This discernible preference underscores the potential for integrating computational learning into medical curricula. The results further reveal a pronounced enthusiasm among students for computational thinking, suggesting a genuine interest in leveraging this approach for clinical problem-based learning. Consequently, it can be posited that the incorporation of computational thinking within medical education and clinical problem-solving scenarios warrants active encouragement in forthcoming educational initiatives.